Modeling interlinkages between sustainable development goals using network analysis - Bali Swain, Ranjula; Ranganathan, Shyam (World development, 2021)
•We investigate the interlinkages between the Sustainable Development Goals (SDGs) indicators.•We further identify the community of interlinked SDG indicators to be benchmarked and prioritized for different regions.•Employing network analysis on IAEG-SDG data, we find that trade-offs tend to be weaker than the synergies.•Analysis for different regions suggests that universal benchmarking of SDGs is counterproductive.•We argue that it is useful to identify and use a community of indicators to prioritize certain SDGs in different regions. Universal, ambitious, and arguably ambiguous, the UN’s Sustainable Development Goals (SDG) are difficult to measure, monitor, prioritize and achieve. They are a multi-dimensional construct of economic, social and environmental indicators that work through complex interlinkages. We investigate these interlinkages at the SDG target level to identify the trade-offs and synergies between the SDGs. Second, we identify the community of interlinked SDG targets to determine if the SDGs can be benchmarked and prioritized for different regions. Employing network analysis approach the analysis is based on the IAEG-SDG data for the period 2000–2017. We find several positive and negative interlinkages (reinforcing and balancing feedbacks) between the SDG targets. The trade-offs, however, are much weaker than the synergies. Analyzing network structures for different regions, our results suggest that universal benchmarking of SDGs is counterproductive. We argue that it may be useful to identify a specific community of SDG targets, and use them as a guide to prioritize certain goals in different regions.